MATERNAL ANTIBODY OF DOC PELUNG FROM COMBINE ND-VACCINATED HEN - Prabowo, D (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2003)
A research entitled ?Maternal Antibody of Pelung Day Old Chicken From Combine ND-Vaccinated Hen? has been done at Deddy Farm, Brebes. The materials were 25 hens and 5 cocks parental Pelung and 50 DOC (day old chick) hatched from those parent. Completely Randomized Design was performed in this experiment. The treatment consists of double dosages of inactive ND vaccine, active ND vaccine and cloned ND vaccine. The parameter was the immunity response on the parents and maternal antibody titer of the raised DOC. The results showed that; (1) one dosage of inactive ND vaccine combined with one dosage of active ND vaccine on Pelung chicken, yielding the best immunity response on the parent. The raised DOC also indicates the best maternal antibody titer, (2) giving two dosages of either inactive or active ND vaccine on the parent and the DOC could be analyzed alternatively to obtain a good immunityresponse, (3) the use of one dosage cloned-ND vaccine and one dosage of inactive or active ND vaccine on Pelung chicken yielding a low immunity response on the parent and the raised DOC. (Animal Production 5(1): 11-18 (2003) Key words : Vaccination, Immunity, Maternal, Antibody, Pelung, Chicken